Surgical treatment of thoracic aortic pseudoaneurysm caused by Brucella melitensis - Hong-Wei Guo; Yang-Xue Sun; Jing Sun; Xiang-Yang Qian (Journal of Cardiothoracic Surgery, 2023)
Abstract Thoracic aortic pseudoaneurysm caused by Brucella melitensis is extremely rare with extremely few cases reported to date. Herein, we present the case of a 65 year-old man with a huge pseudoaneurysm of the proximal descending thoracic aorta, involving the left subclavian artery and distal arch. Surgery was performed to replace the proximal descending aorta with a self-made bovine pericardial duct and the left subclavian artery with a 10 mm artificial vessel under deep hypothermic circulatory arrest; the patient recovered uneventfully. However, continued follow-up is required for long-term results.